If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 = 2x + -7(4x + 18) Reorder the terms: 56 = 2x + -7(18 + 4x) 56 = 2x + (18 * -7 + 4x * -7) 56 = 2x + (-126 + -28x) Reorder the terms: 56 = -126 + 2x + -28x Combine like terms: 2x + -28x = -26x 56 = -126 + -26x Solving 56 = -126 + -26x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '26x' to each side of the equation. 56 + 26x = -126 + -26x + 26x Combine like terms: -26x + 26x = 0 56 + 26x = -126 + 0 56 + 26x = -126 Add '-56' to each side of the equation. 56 + -56 + 26x = -126 + -56 Combine like terms: 56 + -56 = 0 0 + 26x = -126 + -56 26x = -126 + -56 Combine like terms: -126 + -56 = -182 26x = -182 Divide each side by '26'. x = -7 Simplifying x = -7
| X+4=34-4x | | 3q+6=20 | | 6r^2+r=1 | | 26=3x+2x-9 | | x(x+7)+-12(x+7)=0 | | 9x(3x-20)=74 | | 49s^2-81d^2= | | 2(3n-3)=30 | | x(x+11)-18(x+11)=0 | | 9y^2-18y+5=0 | | -19.95+1.10x=18 | | 9y^2-9y+2=0 | | 12-5x-25x^2=0 | | -19.95+1.10x=-1.35 | | u^2+7a^2+6=0 | | 3ln(x+6)=15 | | 2=15z^2+2 | | M+3m+0.5m=36 | | 31n(x-6)=15 | | 81-3x=45 | | 4x+28=30 | | 4w-2w-w+w-w=18 | | 7x-4x-2x-x+x=16 | | 2+3x+1=6x | | 3(2-x)=6 | | 16h+5h-20h=14 | | 7a+a+3a-9a=6 | | 14x+20y=12775 | | 7a+a+3a-9a= | | 16z-15z=20 | | 5(x+4)=2x+20+2x | | 6q-2q=16 |